Hammarskjöld"s interpretation of the Bible - Huls, Jos (HTS teologiese studies, 2010)
This article describes the use of the Bible in Dag Hammarskjöld’s famous and widely read publication, Markings (1988). It asks the question whether his use of the Bible reflects his personal experiences or whether it reflects his search for understanding the meaning of his vocation. The article focuses particularly on the relationship between Scripture and the awakening to the mystical process as it comes to the fore in his discussion of the Johannine passage on Jesus’ washing of the disciple’s feet before the Last Supper (Jn 13–14). In the first section of the article a new, precise version of the text in Markings is provided. Then, secondly, Hammarskjöld’s interpretation and representation of the contents of the passage are analysed. Finally, some general conclusions about the nature of the mystical process in Hammarskjöld’s appropriation of Scripture are given.